Inequality, macroeconomic performance and political polarization: A panel analysis of 20 advanced democracies - Christian Proa\~no Acosta; Juan Carlos Pe\~na; Thomas Saalfeld (Bamberg University, Bamberg Economic Research Group (BERG), 2020)
This paper investigates the macroeconomic and social determinants of voting behavior, and especially of political polarization, in 20 advanced countries using annual data ranging from 1970 to 2016 and covering 291 parliamentary elections. Using a panel estimation approach and rolling regressions, our analysis indicates that a significant change in the link between income inequality and political polarization appears to have taken place over the last twenty years. Indeed, we find that both average inequality, measured by the post-tax Gini coefficient, as well as the bottom 10%income share are statistically linked to the recent success of far-right parties, while the top 10% or top 20% incomes shares are not. The link of income inequality and political polarization thus seems to be based on the deterioration of the relative economic position especially of the poorest fraction of the population. Furthermore, we find no empirical support for the notion that social and economic globalization has led to an increase in the popularity of far-right parties.
Keywords: P16; D6; D72; O15; 330; Income Inequality; Political Polarization; Globalization; Economic Voting Behavior